2006
DOI: 10.1108/00012530610713605
|View full text |Cite
|
Sign up to set email alerts
|

Customers, relationships and libraries: University of Malta – a case study

Abstract: PurposeThe purpose of this research is to analyse the results of a survey conducted in 2003/2004 with regard to the relationship between the University of Malta Library and its customers. Changes to service delivery subsequent to the survey are outlined.Design/methodology/approachResults from a series of focus groups, held with library staff and customers were analysed and are discussed in the paper.FindingsLibrary customers were bypassing the library services and seeking information elsewhere. Demands for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…The results from the Malta study are reported in some detail in an earlier paper (see Broady‐Preston and Felice, 2006). However, a cross‐case comparison enables an exploration of:the suitability of the methodology adopted;the extent to which such studies are transferable across national boundaries; andany similarities or differences in the findings, which may illuminate further studies in this field.Furthermore:… the use of multiple‐case applications in the study emphasizes the complexity of the CRM field and develops the empirical evidence to support and sharpen the theory (Curry and Kkolou, 2004, p. 317, citing Yin, 1994).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The results from the Malta study are reported in some detail in an earlier paper (see Broady‐Preston and Felice, 2006). However, a cross‐case comparison enables an exploration of:the suitability of the methodology adopted;the extent to which such studies are transferable across national boundaries; andany similarities or differences in the findings, which may illuminate further studies in this field.Furthermore:… the use of multiple‐case applications in the study emphasizes the complexity of the CRM field and develops the empirical evidence to support and sharpen the theory (Curry and Kkolou, 2004, p. 317, citing Yin, 1994).…”
Section: Methodsmentioning
confidence: 96%
“…Differing numbers of group interviews were conducted during the two surveys. In Malta, the primary purpose was to ascertain explanations of relatively low usage levels amongst the full range of library customers during a period of rapid expansion within the institution (Broady‐Preston and Felice, 2006). Conversely, the focus of the Coventry study was to examine the relationship existing between the library and the academic staff, during a period of significant change within the university, including changes in departmental structure and a planned programme of voluntary redundancies amongst staff.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The necessity for clear and effective policies related to the identification, development and valuation of intangible assets, as well as the study of intangible resources and the impact of investments made to them is growing for attaining economic goals as well as meeting user requirements. A survey conducted by Broady‐Preston and Felice (2006) in 2003/2004, focusing on analyzing the relationships between the University of Malta Library and its users, concludes that the ongoing bypass of the library services by its users can be reversed by actions such as the improvement of the technology infrastructure, the training of the staff and its customers (students and academics), the enrichment of the collection and the collaboration between academics and subject specialists. The majority of these actions (staff training, enrichment of the information value of the library's collection, training of the customers and development of collaborations) require investments in intangible assets embodied in all intangible assets categories, i.e.…”
Section: Issues For Managing Intangible Assets In Academic Librariesmentioning
confidence: 99%
“…For our purposes, in thinking about the value of information and library services, we need to remember that value is concerned with ideas around fitness for purpose (functional value,) social value (is this usage of information or library service expected of me), emotional value, desire for knowledge (which may overcome other irritations about the service) and the context (which is also dynamicvalue judgements are not stable). Value is personal and relativeit can be enhanced according to proponents of customer relationship management (Broady-Preston and Felice, 2006). Customer value discovery research seeks to find out not only the major aspects valued but also the major irritants (McKnight, 2007).…”
mentioning
confidence: 99%